Sinopsis de los mamíferos silvestres del estado de Guanajuato, México, y comentarios sobre su conservación - Sánchez, Oscar (THERYA, 2014)
Introduction. Alfred Dugès (1826-1910) began the formal study of wild mammals in the state of Guanajuato, Mexico. After his death the subject remained virtually forgotten for almost a hundred years. In the early years of the XXI century several authors began a period of revision of this state fauna based on recent field surveys, museum specimens and previously unnoticed literature. Objectives. The objectives of the present contribution were: to integrate a synopsis of the mammalian fauna of Guanajuato, documenting details for species and subspecies, recognizing proportions of its components at the family level; diagnose the current state coverage of records at the municipality level; outline general biogeographic affinities of the mammal fauna; develop a general conservation view with emphasis on endangered species and protected areas (but without losing sight of other species, spaces and policy instruments), and indicate pending aspects. Methodology. Results of previous literature reviews and museum specimen searches served to summarize mammal species richness, general state distribution and conservation status of taxa. Faunal affinities were outlined considering mammal species whose distribution is clearly associated with large physiographic-biogeographic regions converging in Guanajuato. Information on species at risk, protected areas, priority species, species management units and trade regulations, was gathered and collated to build an integrated conservation diagnostic. Lack of information on other conservation aspects was also addressed and main gaps were identified. Results. Ninety three species of 20 mammal families are known from Guanajuato, mainly Rodentia, Chiroptera and Carnivora. Records were found for 30 of 46 municipalities; but are still unrepresentative. Only 25 species have been recorded in more than five municipalities. The mammal fauna has affinity with the Mexican Plateau, with the slopes of the Gulf of Mexico and of the Pacific, and the Neovolcanic Belt. Most of the territory in Guanajuato is considerably disturbed; main conservation strongholds for species at risk are related to protected areas. Discussion and Conclusions. The 93 recorded species were catalogued with data on subspecies, general state distribution, and comments on taxonomy and conservation status. Guanajuato still needs systematic sampling; current records are not yet representative of the territory. This mammal fauna is a complex with different biogeographical components, which should guide any conservation strategy. Alteration of territory calls for effective conservation within protected natural areas (PNA), particularly for species at risk, but some PNAs do not have a validated mammal inventory. Management units (UMA) are scarce and aim at fostering a few species of economic interest; these units need to reorient their overall support for conservation of native biota. Some species are officially considered as priority ones, which can induce/enhance conservation in Guanajuato. Besides deepening the knowledge of species per se, several conservation aspects are pending, as examples: generate management plans for species at risk in PNAs and outside them, check the operation of UMA with emphasis on the subspecies of whitetail deer that have been introduced and managed, combat exotic and invasive species in the wild (this includes reducing extensive grazing), and characterize the social perception about conservation of mammals and their natural habitat.